THE EFFECTIVENESS OF THE USE OF RPP BY FIELD PRACTICE TEACHERS (PL) IN THE LEARNING PROCESS AT THE STATE HIGH SCHOOL OF 1 TONDANO - Yoseph Daniel Arie Santie; Romi Mesra; Rahayu Rahayu (Lembaga Penelitian dan Pendidikan Mandala, 2022)
One of the most important things that must be prepared before teaching in schools is the lesson plan (RPP) which has also been previously taught on campus in the Microteaching course. This lesson plan needs to be prepared by the PL teacher from the start so that students have guidelines in teaching. The purpose of this study is to reveal the extent to which the use of lesson plans by field practice teachers in the learning process at SMA Negeri 1 Tondano. The method used is a qualitative research method where this method basically looks at a phenomenon or social reality and then analyzes it using the researcher's own point of view. There are three lines of qualitative data analysis, namely data reduction, data presentation, and drawing conclusions. The results of this study are as follows: 1. Field Practice Teachers (PL)Â do not really understand the use of RPP in PBM as a whole, 2. PBM implementation is carried out spontaneously not based on RPP, 3. RPP helps Field Practice Teachers (PL)Â on certain components during PBM, 4. Some Field Practice Teachers (PL)Â try to use lesson plans as much as possible in PBM, 5. PL teachers face many obstacles in using lesson plans in PBM